A novel temperature‐controlled device with standardized manipulation improves chronic back pain mediated by modulating deep muscle thickness: A multicenter randomized controlled trial - Li Li; Ying Wang; Yinqiu Gao; Shu Liu; Guangjing Yang; Xiaoying Lv; Ya Xuan Sun; Ying Wu; Jinlin Li; Jiayan Zhou; Guang Chen (Wiley, 2024)
Abstract Background Chronic back pain affected 619 million people globally in 2020 which accounts for a heavy disease burden causing tremendous productivity losses. Current therapies including ibuprofen, duloxetine, and opioids might cause side effects and even severe drug use disorders. Therefore, a non‐pharmacologic therapy with better or equivalent efficacy and fewer side effects is needed. Methods We did a multi‐center, single‐blinded, randomized, positive drug controlled, clinical trial. Patients with chronic back pain in moderate severity were randomized into receiving hot stone massage or flurbiprofen plaster group. Both interventions were 2 weeks with a follow‐up of 4 weeks. The primary outcome was the change in the score of the Global Pain Scale (GPS) from baseline to week 2. Secondary outcomes included Numerical Rating Scale (NRS), Chronic Pain Acceptance Questionnaire (CPAQ), Pain Self‐Efficacy Questionnaire (PSEQ), Hospital Anxiety and Depression Scale (HADS), and Short Form‐36 (SF36) from baseline to week 2 and week 6. Exploratory outcome assessment included the muscle thickness measured by ultrasound. Any adverse event was monitored throughout the study period. Results A total of 120 patients were enrolled in this trial. At 2 weeks GPS decreased significantly in the hot stone massage group compared to the flurbiprofen group (difference between groups = ‐8.1 points, 95% confidence interval [CI] ‐15.8 to ‐0.3, p = 0.047). Moreover, hot stone massage also showed more improvement at 2 weeks compared to flurbiprofen, including NRS (‐0.5 points, 95% CI ‐1.0 to ‐0.1, p = 0.029), PSEQ (5.4 points, 95% CI 0.5 to 10.2, p = 0.030), and mental component of Short Form‐36 (SF‐36) (1.7 points, 95% CI 0.4 to 2.9, p = 0.010), but not in CPAQ (p = 0.131), HADS (p = 0.303 for depression, p = 0.399 for anxiety), or SF‐36 (p = 0.129 for physical component, p = 0.246 for social component, p = 0.076 for fatigue component). A total of two participants in the hot stone massage group reported mild pain on skin surface when receiving the procedure at the first intervention session.